The influence of aspirin resistance on non-fatal coronary events following percutaneous coronary interventions - Catakoglu, Alp B.; Aytekin, Saide; Celebi, Huseyin; Sener, Murat; Kurtoglu, Hilal; Demiroglu, Cemsid; Aytekin, Vedat (Archives of Medical Science, 2009)
Introduction: Aspirin resistance is associated with unfavourable prognosis, including a higher incidence of myocardial infarction, stroke, and cardiovascular death among stable cardiovascular patients, a higher incidence of re-occlusion after peripheral angioplasty, and myonecrosis following elective percutaneous coronary interventions (PCI). The objective of this study was to evaluate the relationship between aspirin resistance and non-fatal clinical endpoints during the long term follow-up following successful PCI. Material and methods: A total of 100 subjects with angiographically diagnosed coronary artery disease and treated with elective, non-urgent intracoronary stent implantation between October 2001 and June 2002 were enrolled in the study. All patients were under regular aspirin (300 mg) treatment. PFA-100 analyzer was used to assess the platelet functions. Aspirin resistance was defined as a collagen/epinephrine closure time (CTCEPI) < 186 s. The study end-point was the composite of non-fatal coronary events which included non-fatal MI, coronary artery bypass graft surgery (CABG) or repeat PCI, during the 2-year follow-up period after the index PCI. Results: The incidence of aspirin resistance was found to be significantly higher (p = 0.021) in patients with non-fatal coronary events (22.4%) compared to those who did not have (5.9%). Aspirin resistance was found to be an independent risk factor for non-fatal coronary events after adjusted for other potential risk factors (p = 0.019). Conclusions: Despite regular treatment with aspirin, the incidence of aspirin resistance was significantly higher in patients who developed non-fatal coronary events on long term follow-up following elective PCI. Thus, these findings suggest that aspirin resistance might be an important risk factor that could affect the outcome following PCIs.